Psychotraumatology in Europe: a personal history - Stuart Turner (European Journal of Psychotraumatology, 2013)
This paper outlines a personal account of the growth of the field of traumatic stress in Europe, especially with the history of major disasters in the 1980s, the first European Conference in Lincoln in 1988, the formation of European Society for Traumatic Stress Studies and its subsequent development, for example, with a federal structure and its own journal, and most important of all the way that the field as a whole has matured.